Writing Orthotic Device for the Management of Writer’s Cramp - Singam, Narayanasarma V.; Dwivedi, Alok; Espay, Alberto J. (Frontiers in Neurology, 2013)
Background: Oral therapies and chemodenervation procedures are often unrewarding in the treatment of focal, task-specific hand disorders such as writer's cramp or primary writing tremor. Methods: A portable writing orthotic device was evaluated on fifteen consecutively recruited writer's cramp and primary writing tremor subjects. We measured overall impairment at baseline and after two weeks of at-home use with the Writer’s Cramp Rating Scale (range = 0-8, higher is worse) and writing quality and comfort with a visual analog scale (range = 0-10). Results: Compared to regular pen, the writing orthotic device improved the Writer's Cramp Rating Scale scores at first-test (p=0.001) and re-test (p=0.005) as well as writing quality and device comfort in writer's cramp subjects. Benefits were sustained at two weeks. Primary writing tremor subjects demonstrated no improvements. Conclusions: Writing orthotic devices exploiting a muscle-substitution strategy may yield immediate benefits in patients with writer's cramp.